Identification and characterization of a novel β-glucosidase via metagenomic analysis of Bursaphelenchus xylophilus and its microbial flora. Issue 1 (December 2017) - Zhang, Lin; Fu, Qiang; Li, Wenpeng; Wang, Bowen; Yin, Xiaoyan; Liu, Suyao; Xu, Zhaonan; Niu, Qiuhong
Abstract β-glucosidases catalyze the final step of cellulose hydrolysis and are essential in cellulose degradation. A β-glucosidase gene, cen502, was identified and isolated from a metagenomic library fromBursaphelenchus xylophilus via functional screening. Analyses indicated thatcen502 encodes a 465 amino acid polypeptide that contains a catalytic domain belonging to the glycoside hydrolase family 1 (GH1). Cen502 was heterologously expressed, purified, and biochemically characterized. Recombinant Cen502 displayed optimum enzymatic activity at pH 8.0 and 38 °C. The enzyme had highest specific activity to p-nitrophenyl-β-D-glucopyranoside (pNPG; 180.3 U/mg) and hadK m andV max values of 2.334 mol/ml and 9.017 μmol/min/mg, respectively. The addition of Fe2+ and Mn2+ significantly increased Cen502 β-glucosidase activity by 60% and 50%, respectively, while 10% and 25% loss of β-glucosidase activity was induced by addition of Pb2+ and K+, respectively. Cen502 exhibited activity against a broad array of substrates, including cellobiose, lactose, salicin, lichenan, laminarin, and sophorose. However, Cen502 displayed a preference for the hydrolysis of β-1, 4 glycosidic bonds rather than β-1, 3, β-1, 6, or β-1, 2 bonds. Our results indicate that Cen502 is a novel β-glucosidase derived from bacteria associated withB. xylophilus and may represent a promising target to enhance the efficiency of cellulose bio-degradation in industrial applications.